2020
DOI: 10.1111/papr.12965
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Adherence to Pain Management in Advanced Cancer Patients

Abstract: Aim To assess patients’ barriers to pain management and analgesic medication adherence in patients with advanced cancer. Methods This was a prospective cross‐sectional study in patients with advanced cancer receiving chronic opioid therapy. Age, gender, cancer diagnosis, Karnofsky level, and educational status were recorded. The Brief Pain Inventory (BPI), Edmonton Symptom Assessment Scale (ESAS), Memorial Delirium Assessment Scale (MDAS), Barriers Questionnaire II (BQ‐II), Medication Adherence Rating Scale (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Yates et al also found that the majority of patients stated addiction to medication as a barrier and believed in a real risk of addiction (Yates et al., 2002). Patients in the study of Mercadante et al identified constipation, nausea, vomiting and a feeling of tiredness and lethargy as worrying side effects of analgesics and avoided taking the medication (Mercadante et al., 2021). Opioids side effects and fear of addiction have also highlighted as attitudinal barriers by participants of the previous studies (Konstantis & Exiara, 2018; Kwon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yates et al also found that the majority of patients stated addiction to medication as a barrier and believed in a real risk of addiction (Yates et al., 2002). Patients in the study of Mercadante et al identified constipation, nausea, vomiting and a feeling of tiredness and lethargy as worrying side effects of analgesics and avoided taking the medication (Mercadante et al., 2021). Opioids side effects and fear of addiction have also highlighted as attitudinal barriers by participants of the previous studies (Konstantis & Exiara, 2018; Kwon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The BAROC is an exploratory study investigating the relationship between psychological barriers and improvement in pain. It is important to use PROs, as pain improvement contributes to health-related quality of life 36–39. Psychological barriers may be influenced by opioid switching and analgesic use before the commencement of regular strong opioid analgesics use 18 36 40.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to use PROs, as pain improvement contributes to health-related quality of life 36–39. Psychological barriers may be influenced by opioid switching and analgesic use before the commencement of regular strong opioid analgesics use 18 36 40. These data are also being collected using the EDC system.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge among physician and patients, lack of adequate supply of opioids as well as limited access to palliative care services are the main causes of inadequate pain control in countries with limited resources [ 15 ]. Besides this, opioids-related adverse events remain the most important barriers that interfere with adherence to opioid analgesics [ 16 ].…”
Section: Discussionmentioning
confidence: 99%